Video and image systems engineering education for the 21st century - Zoltowski, Michael D., author; Shroff, Ness B., author; Pizlo, Zygmunt, author; Maciejewski, Anthony A., author; Landgrebe, David A., author; Delp, Edward J., author; Coyle, Edward J., author; Bouman, Charles Addison, author; Allebach, Jan P., author; IEEE, publisher (Colorado State University. Libraries, 1996)
We are developing a new graduate program at Purdue in Video and Image Systems Engineering (VISE). The project is comprised of three parts: a new curriculum centered around a degree option in VISE to be earned as part of the Masters or Ph.D. degrees; a state-of-the-art lecture/laboratory facility for instruction, laboratory experiments, and project and homework activities in VISE courses; and enhancement of existing courses and development of new courses in the VISE area.
Keywords: educational courses; electrical engineering education; image processing; systems engineering; video signal processing